2013
DOI: 10.1603/an12090
|View full text |Cite
|
Sign up to set email alerts
|

Review and Key for the Identification of Parasitoids (Hymenoptera: Braconidae: Aphidiinae) of Aphids Infesting Herbaceous and Shrubby Ornamental Plants in Southeastern Europe

Abstract: Original information on aphidiines parasitizing aphids on herbaceous and shrubby ornamental plants in southeastern Europe is presented. In total, 22 species are keyed and illustrated with scanning electron micrographs, stereomicroscope micrographs, and line drawings. The aphidiines presented in this work have been identified from 40 aphid taxa. Two hundred sixty-six aphidiine— aphid—plant associations are presented, out of which 126 are new. The results are discussed in relation to the overall parasitoid—aphid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 36 publications
1
27
0
1
Order By: Relevance
“…Very reach data on many trophic associations (primary parasitoids -aphid host -host plants), including areas of cities from southeastern regions of Europe were recorded by Kavallieratos et al (2004Kavallieratos et al ( , 2013 and Tomanović et al(2006Tomanović et al( , 2009. These authors mentioned many plant species as reservoirs of primary parasitoids of aphids, including urban environments, such as: Salix spp., Malus spp., Prunus spp., Spiraea spp., Berberis spp., Betula spp., F. australis, Sambucus spp., Acer spp., Tilia spp., Fagus spp., Evonymus spp., Viburnum spp., Philadelphus spp., Lonicera spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very reach data on many trophic associations (primary parasitoids -aphid host -host plants), including areas of cities from southeastern regions of Europe were recorded by Kavallieratos et al (2004Kavallieratos et al ( , 2013 and Tomanović et al(2006Tomanović et al( , 2009. These authors mentioned many plant species as reservoirs of primary parasitoids of aphids, including urban environments, such as: Salix spp., Malus spp., Prunus spp., Spiraea spp., Berberis spp., Betula spp., F. australis, Sambucus spp., Acer spp., Tilia spp., Fagus spp., Evonymus spp., Viburnum spp., Philadelphus spp., Lonicera spp.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is a need to estimate trophic relationships between aphid communities and plant community structures. Urban environments can be reservoirs of aphids, including pests and of natural enemies of aphids which was recorded in literature data, such as Kavallieratos et al (2004Kavallieratos et al ( , 2013 and Tomanowić et al (2006Tomanowić et al ( , 2009.…”
Section: Introductionmentioning
confidence: 95%
“…Only one primary parasitoid, L. testaceipes, was recovered consistently from A. nerii mummies regardless of host plant species. However, in other geographical areas of the world (i.e., southeastern Europe) the parasitoid spectrum of A. nerii is complex even in areas where the Nearctic species L. testaceipes has been well established (Kavallieratos et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Lysiphlebus testaceipes (Cresson) was the dominant primary parasitoid recovered during both studies. Extensive investigations in southeastern Europe showed that the Aphidiinae spectrum of A. nerii on oleander is composed of seven species, i.e., Aphidius colemani Viereck, Binodoxys angelicae (Haliday), Diaeretiella rapae (M'Intosh), Lysiphlebus confusus Tremblay and Eady, Lysiphlebus fabarum (Marshall), L. testaceipes and Praon volucre (Haliday) (Kavallieratos et al, 2001(Kavallieratos et al, , 2004(Kavallieratos et al, , 2006(Kavallieratos et al, , 2013Tomanović et al, 2009;Ž ikić et al, 2012). In a recent study Kavallieratos et al (2013) reported that A. colemani is the dominant parasitoid species of A. nerii on N. oleander in the geographical area of southeastern Europe and suggested that the cultivation of this plant should be seriously taken into consideration in the design of green public areas.…”
mentioning
confidence: 99%
“…Braconid Hymenoptera were Þrst separated using the criteria of Goulet and Huber (1993) using a Leica MZ16 stereomicroscope. Aphidiine wasps were then separated and identiÞed based on morphological criteria described by Starý (1973Starý ( , 1976; Gärdenfors (1986); Kavallieratos et al (2001Kavallieratos et al ( , 2005Kavallieratos et al ( , 2013; Tomanović and Kavallieratos (2002); Tomanović et al (2003Tomanović et al ( , 2007a; and Barahoei et al (2013) Statistical Analysis. Statistical analyses were performed using R 3.0 (R Development Core Team 2013).…”
Section: Methodsmentioning
confidence: 99%